2019
DOI: 10.1101/668541
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting the Autonomic Nervous System Balance in Patients with Chronic Low Back Pain using Transcranial Alternating Current Stimulation: A Randomized, Crossover, Double-Blind, Placebo-Controlled Pilot Study

Abstract: BackgroundChronic low back pain (CLBP) is characterized by an alteration in pain processing by the central nervous system that may affect autonomic nervous system (ANS) balance. Heart rate variability (HRV) reflects the balance of parasympathetic and sympathetic ANS activation. In particular, respiratory sinus arrhythmia (RSA) solely reflects parasympathetic input and is reduced in CLBP patients. Yet, it remains unknown if non-invasive brain stimulation can alter ANS balance in CLBP patients.ObjectiveTo evalua… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 75 publications
(83 reference statements)
2
2
0
Order By: Relevance
“…Bayesian statistics to strengthen the interpretability of negative findings [7]. However, complementing the weak tACS effects on pain in previous studies [1,5,35], we did not find significant tACS effects on tonic experimental pain in healthy human participants.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Bayesian statistics to strengthen the interpretability of negative findings [7]. However, complementing the weak tACS effects on pain in previous studies [1,5,35], we did not find significant tACS effects on tonic experimental pain in healthy human participants.…”
Section: Discussionsupporting
confidence: 82%
“…However, tACS induced changes of alpha activity which correlated with pain intensity [1]. In addition, exploratory analyses of autonomic activity recorded in this study indicated that heart rate variability was increased [35]. Our study extends these findings in two important aspects.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations